Mrs. MacSwiney's American visit (1920)
Group of female activists with protest placards and American flags around a motor car at an unidentified location. Protest condmening American relations with England during the Irish War of Independence was held during Muriel MacSwiney's tour of the United States.
Title and date inscribed on verso "Dec., 1920".
catalogued
Keywords: MacSwiney, Muriel, -- 1892- -- Travel -- United States; Women political activists -- United States; Protest posters -- American -- 1910-1930; Activists -- United States -- 1910-1920; Ireland -- History -- 1910-1921; Photographic prints -- Irish -- 1910-1920